Alinhamento das expectativas e mensuração dos resultados do processo de coaching executivo – uma análise a partir das perspectivas dos três atores envolvidos: coachee, decisores da empresa e coach - Vieira, Marcia Michel (Universidade do Vale do Rio dos Sinos, 2021)
Executive coaching has been one of the main strategies for developing leadership skills (ALBIZU, 2019). However, the analysis of results presents opportunities of improvement. According to Grover e Furnham (2016), most researches involving the evaluation of results are still exclusively based on the perceptions of the satisfaction of the actors involved. In view of this, this study aims to analyze how expectations are aligned and how the results of executive coaching processes are evaluated in the perspective of the three actors: the coachee, the company decision-makers and the coach. Based on the theoretical study, an exploratory field research was carried out, interviewing 15 individuals and using instruments specifically developed for each actor. The interviewees work in the states of Rio Grande do Sul (RS), Santa Catarina (SC), São Paulo (SP) and Acre (AC) in different segments, such as industry, a financial institution, an industry representation entity, civil construction and retailing. NVivo software was used in the analysis. It is presented through the analysis of the interviews: the a priori categories and their relationship with the theoretical framework and the research objective. In this sense, the executive coaching process is addressed considering the context of the individual and the organization. It was identified that the actors involved in the executive coaching processes reveal satisfaction with the results and that the expectations and the perception of the achievement of objectives are aligned. However, this assessment is exclusively based on perceptions and a qualitative assessment is not carried out. A qualitative assessment may become a differential, especially from the perspective of the sponsoring company. Finally, as a managerial contribution, a framework is proposed for the execution of a sponsored executive coaching process aiming at an alignment between the expectations and the evaluation of results, suggesting the inclusion of quantitative indicators, which added to the qualitative evaluation, prove the effectiveness of executive coaching.
Keywords: Coaching executivo; Desenvolvimento de competências; Gestão de recursos humanos; Coaching; Executive; Skills development; Human resource management; ACCNPQ::Ciências Sociais Aplicadas::Administração